Incidence of Spodoptera frugiperda (J.E. Smith) infestation on corn (Zea mays L.) in Enrekang Regency - Asrini Asrini; Hikmahwati Hikmahwati; Muh. Achyar Ardat; Suhardi Suhardi (Department of Plant Pest and Diseases, Faculty of Agriculture, Hasanuddin University, 2025)
Corn continues to be a crucial food crop in Indonesia, often serving as a rice substitute. Additionally, it holds strategic importance due to its substantial impact on economic stability. Production in Enrekang Regency has experienced fluctuations. Several factors contribute to declining corn production, one of which is the invasion of new pests that cause severe crop damage, Spodoptera frugiperda (J.E. Smith), known as Fall Armyworm (FAW). The pest targets the plant's growing point, potentially causing shoot failure and stunted growth, leading to reduced corn productivity. Based on this background, research is needed on the pest attack rate. The FAW on corn as part of efforts to monitor its presence. This research was conducted in Enrekang Regency, which collected field data on infestation intensity, and then integrated them with pest damage intensity assessment criteria. The observation found that FAW infestation intensity in the Cendana, Maiwa, and Enrekang Districts of Enrekang Regency ranges from low to moderate. However, the resulting damage is significant, particularly during the vegetative phase of the plants.